Short communication: First report of Long-tailed Macaque (Macaca fascicularis) at Logending Beach, Indonesia - Rosyid Ridlo Al Hakim; Rizaldi Rizaldi; Erie Kolya Nasution; Siti Rukayah (Jurusan Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2021)
This short communication study reports the first report of the latest condition of long-tailed macaques in Logending Beach (Pantai Logending), Indonesia. Observations were carried out in August 2021. The observation location is close to several community stalls selling around the beach and the leading portal to enter the Logending Beach area. The long-tailed macaque found by observers is still within a distance (<1 km) from the primary forest bordering the Logending Beach. Several long-tailed macaque individuals encountered during the findings and field observations may be separated from the leading group. The body condition of some long-tailed macaques found during the observation seems to be quite good, but the findings have been that there has been human-primate interaction in the form of provisioning food. These observations and findings are still not sufficient to prove the original habitat of long-tailed macaques, so to prove the size of the long-tailed macaque group in Logending Beach and its surroundings, further research is needed as well as to confirm the food diet and anthropogenic influences that occur between long-tailed macaques and residents around at Logending Beach.